Abnormal Blood Bacteriome, Gut Dysbiosis, and Progression to Severe Dengue Disease - Chancharoenthana, Wiwat; Kamolratanakul, Supitcha; Ariyanon, Wassawon; Thanachartwet, Vipa; Phumratanaprapin, Weerapong; Wilairatana, Polrat; Leelahavanichkul, Asada (Frontiers in Cellular and Infection Microbiology, 2022)
Despite a well-known association between gut barrier defect (leaky gut) and several diseases, data on translocation of pathogen molecules, including bacterial DNA (blood bacteriome), lipopolysaccharide (LPS), and serum (1→3)-β-D-glucan (BG), from the gut to the blood circulation (gut translocation) in dengue are still less studied. Perhaps, dengue infection might induce gut translocation of several pathogenic molecules that affect the disease severity. At the enrollment, there were 31 dengue cases in febrile and critical phases at 4.1 ± 0.3 days and 6.4 ± 1.1 days of illness, respectively, with the leaky gut as indicated by positive lactulose-to-mannitol excretion ratio. With blood bacteriome, the patients with critical phase (more severe dengue; n = 23) demonstrated more predominant abundance in Bacteroidetes and Escherichia spp. with the lower Bifidobacteria when compared with the healthy control (n = 5). Meanwhile, most of the blood bacteriome results in dengue with febrile stage (n = 8) were comparable to the control, except for the lower Bifidobacteria in dengue cases. Additionally, endotoxemia at the enrollment was demonstrated in five (62.5%) and 19 (82.6%) patients with febrile and critical phases, respectively, while serum BG was detectable in two (25%) and 20 (87%) patients with febrile and critical phases, respectively. There were higher peripheral blood non-classical monocytes and natural killer cells (NK cells) at the enrollment in patients with febrile phage than in the cases with critical stage. Then, non-classical monocytes (CD14-CD16+) and NK cells (CD56+CD16-) increased at 4 and 7 days of illness in the cases with critical and febrile stages, respectively, the elevation of LPS and/or BG in serum on day 7 was also associated with the increase in monocytes, NK cells, and cytotoxic T cells. In summary, enhanced Proteobacteria (pathogenic bacteria from blood bacteriomes) along with increased endotoxemia and serum BG (leaky gut syndrome) might be collaborated with the impaired microbial control (lower non-classical monocytes and NK cells) in the critical cases and causing more severe disease of dengue infection.